Sustainable management of soil organic matter - Rees, R. M.; Ball, B. C.; Ball, B. C.; Campbell, C. D.; Campbell, C. D.; Rees, R. M.; Watson, C. A.; Watson, C. A. (Wallingford :CABI Publishing, 2001)
This book is divided into 6 sections: organic matter and sustainability; modelling soil organic matter dynamics - global challenges; soil organic matter management - the roles of residue quality in C sequestration and N supply; the role of soil organic matter and manures in sustainable nutrient cycling; implications of soil biodiversity for sustainable organic matter management; and soil teeming with life - new frontiers for soil science.
Keywords: JJ100 - Soil Biology; JJ200 - Soil Chemistry and Mineralogy; JJ600 - Soil Fertility; JJ700 - Fertilizers and other Amendments